Prescribing trends of attention‐deficit hyperactivity disorder (ADHD) medications in UK primary care, 1995–2015. (9th June 2016) - Renoux, Christel; Shin, Ju‐Young; Dell'Aniello, Sophie; Fergusson, Emma; Suissa, Samy
Abstract: Aim: The aim of the present study was to describe the prescription of medications for attention‐deficit hyperactivity disorder (ADHD) in the UK between 1995 and 2015. Methods: Using the Clinical Practice Research Datalink (CPRD), we defined a cohort of all patients aged 6–45 years, registered with a general practitioner between January 1995 and September 2015. All prescriptions of methylphenidate, dexamphetamine/lisdexamphetamine and atomoxetine were identified and annual prescription rates of ADHD were estimated using Poisson regression. Results: Within a cohort of 7 432 735 patients, we identified 698 148 prescriptions of ADHD medications during 41 171 528 person‐years of follow‐up. Usage was relatively low until 2000, during which the prescription rate was 42.7 [95% confidence interval (CI) 20.9, 87.2] prescriptions per 10 000 persons, increasing to 394.4 (95% CI 296.7, 524.2) in 2015, corresponding to an almost 800% increase (rate ratio 8.87; 95% CI 7.10, 11.09). The increase was seen in all age groups and in both sexes but was steepest in boys aged 10–14 years. The prescription rate in males was almost five times that of females. Methylphenidate remained the most prescribed drug during the 20‐year study period, representing 88.9% of all prescriptions in the 6–24‐year‐old group, and 63.5% of all prescriptions in adults (25–45 years of age). Conclusions: Prescription rates of ADHD medications have increased dramatically in the past two decades. This may be due, at least in part, to both an increase in the number of patients diagnosed with ADHD over time and a higher percentage of those patients treated with medication.